2019
DOI: 10.3390/ijms21010095
|View full text |Cite
|
Sign up to set email alerts
|

SP-8356, a Novel Inhibitor of CD147-Cyclophilin A Interactions, Reduces Plaque Progression and Stabilizes Vulnerable Plaques in apoE-Deficient Mice

Abstract: Interactions between CD147 and cyclophilin A (CypA) promote plaque rupture that causes atherosclerosis-related cardiovascular events, such as myocardial infarction and stroke. Here, we investigated whether SP-8356 ((1S,5R)-4-(3,4-dihydroxy-5-methoxystyryl)-6, 6-dimethylbicyclo[3.1.1]hept-3-en-2-one), a novel drug, can exert therapeutic effects against plaque progression and instability through disruption of CD147-CypA interactions in apolipoprotein E-deficient (ApoE KO) mice. Immunocytochemistry and immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Lately, SP-8365—a new inhibitor of the complex CyPA/EMMPRIN—was found effective for the treatment of atherosclerosis by reducing plaque progression and stabilizing vulnerable plaque in apoE-deficient mice [ 28 ]. Here, we found that rather than disrupting the complex, Ivabradine increased the binding between CyPA and LG-EMMPRIN, a low-molecular glycosylation form of EMMPRIN, which was not associated with EMMPRIN-induced MMP expression and activation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, SP-8365—a new inhibitor of the complex CyPA/EMMPRIN—was found effective for the treatment of atherosclerosis by reducing plaque progression and stabilizing vulnerable plaque in apoE-deficient mice [ 28 ]. Here, we found that rather than disrupting the complex, Ivabradine increased the binding between CyPA and LG-EMMPRIN, a low-molecular glycosylation form of EMMPRIN, which was not associated with EMMPRIN-induced MMP expression and activation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang et al [65] found that metuzumab could inhibit metastasis of esophageal cancer via blocking the function of BSG. Furthermore, BSG inhibitors are now being developed and tested [66][67][68], and we hope our study can provide some evidence for BSG targeted treatment of TC. There were still some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BSG inhibitors are now being developed and tested [66][67][68], and we hope our study can provide some evidence for BSG targeted treatment of TC.…”
Section: Discussionmentioning
confidence: 99%